A new mesopterous species of the genus Phryganogryllacris (Orthoptera: Gryllacrididae: Hyperbaeninae) from Shandong, China - Yin, Zi-Xu; Wang, Guo-Li; Shen, Zi-Hao (Zootaxa, 2021)
Phryganogryllacris laoshanica sp. nov. is described from Shandong, China. The new species is the first mesopterous species belonging to the genus Phryganogryllacris. Types of the new species in this paper are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences.